The impact of care management for high-risk pediatric asthmatics on healthcare utilization. (2nd January 2021) - Lou, Yingbo; Atherly, Adam; Johnson, Tracy; Anderson, Mark; Valdez, Carolyn; Sabalot, Sarah
Abstract: Introduction: From 2011 to 2015, a series of quality improvement interventions were developed that targeted pediatric persistent asthmatics that included recalls for those overdue for care and access to specialist care. The objective of this study was to assess the impact on urgent care and emergency department visits and hospitalizations from enrollment into at least one intervention during the time period. Methods: Persistent asthmatics were identified through electronic medical records, with patients having an asthma designation containing "persistent, " asthma control containing "poor", and asthma risk being "high risk." Asthma utilization events were identified for these patients between January 1, 2011, and June 30, 2015 using ICD-9 diagnosis codes. Evaluation focused on differences in utilization for patients before and after receiving interventions through the use of logistic regression for each utilization outcome. Results: The interventions were delivered to 1060 children out of a total of 2046 identified as having the persistent asthmatic criteria. The intervention group consisted of 389 (36.7%) moderate persistent asthmatics and 643 (60.7%) mild persistent asthmatics, with 976 (92.1%) identifying as a minority. Analysis of 60692 months of data showed patients who received the intervention were less likely to visit the urgent care (OR [0.80, 0.96]) or be hospitalized (OR [0.37, 0.75]) than those who did not receive any interventions. Adjustment for provider referral into the interventions resulted in slight changes for both hospitalizations (OR [0.38, 0.79]) and urgent care (OR [0.68, 0.94]). Conclusion: Children receiving interventions were less likely to be hospitalized or visit urgent care clinics.